Ocena trombocitne funkcije z merjenjem adhezije in agregacije trombocitov na polistirenski membrani pri bolnikih z esencialno trombocitemijo - Reberšek, Katarina (Zdravniški vestnik, 2008)
Background People with essential thrombocythemia (ET) have increased number ofcirculating platelets. The function of platelets is often impaired. Some people with ET can suffer from bleeding or clotting due to their disease. Acetylsalicylic acid (ASA) may be useful in treating patients with symptoms ofmicrovascular occlusion. Numerous methods for evaluation of platelet function are available. Most of them have numerous disadvantages. In this research a new method adhesion and aggregation on polystyrene surface (AAPS) was assessed. Methods The research comprised 69 patients with ET. The study group consisted of 49 patients that were treated with ASA and 20 patients thatwere not treated with ASA. We measured platelet aggregation using aggregometer and closure time. We were also testing platelet function using the new method AAPS. The measured values were compared to values of healthy subjects. Results Surface coverage (3.3% vs. 1,7%) and average size of platelets and platelet aggregates (45 m2 vs. 32 m2) of the modified test AAPS were decreased for patients that were not treated with ASA versus healthysubjects (p < 0.05). Surface coverage (1.7% vs. 11%), average size of platelets and platelet aggregates (32 m2 vs. 42 m2) and number of platelets and platelet aggregates (263 vs. 1421) of the modified test AAPS for patients that were treated with ASA versus patients that were not treated with ASA wereincreased (p < 0.05). Conclusions We found out that the AAPS modified testis useful for evaluation of platelet dysfunction in patients with ET. Furthermore the AAPS modified test is suitable for monitoring treatment with ASA and screening patients with acetylsalicylic acid resistance . We also found out that the number of platelets in blood exerts influence upon number of platelets and platelet aggregates measured by the standard test AAPS.
Keywords: agregacija; Aspirin; esencialna trombocitemija; hematologija; motnje; Platelet Aggregation; Platelet Function Tests; Thrombocythemia, Hemorrhagic; Trombocitemija hemoragična; trombociti; Trombociti, agregacija; Trombociti, funkcijski testi